PERANCANGAN GAME EDUKASI HAPPY PUDING BERBASIS MULTIMEDIA - Kurniawati, Dina (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
The purpose of the thesis writing educational game Happy pudding is to produce a game that can help teach you how to work materials of food and fruits in the process of making pudding. The usefulness of this game is to help players learn the materials commonly used to make pudding while playing, adding to the knowledge of a player who had not known about the benefits and nutrients contained in food ingredients and fruit in the pudding expected to know after playing this game , as learning how to make pudding and entertainment for children, adolescents, or adults